Outcome of Minimally Invasive Percutaneous Plate Osteosynthesis Using Locking Compression Plate for Distal Tibial Fractures - Sagar Rampure; Harsh Choraria; Krishna Hanchate; Sujay K Mahadik; Shrikant Deshpande (International Journal of Integrated Health Sciences)
Objectives: To assess the functional and radiological outcomes of the distal tibia fractures managed surgically with a locking compression plate by MIPPO technique.